The Sociology of Knowledge in Pesantren: Sanad, Sorogan-Bandongan, and the Making of Intellectual Authority - Indrawan Cahyadi; Ahmad Yunani; Muhammad Dachlan; Ahmad Suhendra (AL-TAHRIR, 2025)
Pesantren intellectuals played an important role in the history of Islamic civilization in the archipelago, acting as a place to preserve and develop Islamic science from the first kings in the modern period. This research uses qualitative methods with a sociology of knowledge approach. This approach is combined with a historical-sociological perspective. This combination allows the research not only to describe the practices of knowledge transmission but also to uncover the social structures and epistemological meanings that underpin the legitimacy of ulama and the intellectual networks of Pesantren. This research aims to provide a complete image of four main directions: The intellectual network of Pesantrens, the Intellectual discourse that is built, the mechanism of knowledge dissemination and the network of scholars are formed. First, the intellectual scope of the pesantren is understood as the history of institutions that combine the tradition of the golden book, practice sulfur and local social dynamics, thus creating unique Intellectual habits. Second, the Intellectual discourse of Pesantrens is carried out through research programs based on Nadhir, Syarah and Hasyiah, where the process of Tarjih and Takhrij encourages internal criticism while maintaining the authenticity of the Sanad. Third, the dissemination of knowledge occurs by the personal relationship between the methods of Kyai and Santri, Bandongan, Sorogan and Halaqah, strengthened by the Sanad Diploma; This model results in a structured and sustainable community of researchers. Fourth, the network of pesantren transcends geographical boundaries, formed by the activities of Santri in Islamic research centers in the Middle East and once again distributing new domestic knowledge and methods, creating a transnational network. Adaptive distribution and network models reinforce the role of considering maintaining the continuity of Islamic science and expanding its effects on a global scale.